Survey of Nurses' Educational Needs Related to End of Life Care - Schlairet, Maura C. (My University, 2006)
A decade after release of the landmark Study to Understand Prognoses and Preferences for Outcomes and Risks of Treatment, improvements in end of life (EOL) care are apparent. Notwithstanding an improved dialogue focused on EOL care, evidence suggests persistent shortcomings in our ability to meet the needs of the dying. Registered Nurses must possess the knowledge/skill to assist patientslfamilies in managing health across all stages of life, including the EOL phase. A significant proportion of practicing nurses have not received formal EOL care education. Of further concern, deficiencies in existing formal EOL care education have been well described. Insufficient information exists on specific EOL care educational needs of practicing RNs. Few surveys exploring educational needs of nurse generalists have been available and no large-scale utilization of any one instrument has been identified. To aid in development of EOL continuing education (CE) for RNs, a survey was designed to explore nurses' EOL care attitudebelief, knowledge/skill, education, and learner characteristics. The survey was published in a state nurse association newspaper and mailed to all RNs in one southeastern state. A Web-based version of the survey was also available. The accessible population consisted of 5 1,000 licensed RNs. Return of 567 surveys, primarily via the Web, resulted in a response rate of 1.1 %. Reliability was assessed with calculation of coefficient alpha of 0.96 across survey sections. The majority of respondents had neither formal EOL education nor prior EOL CE. Yet, nurses held positive attitudebelief toward EOL care and the majority desired EOL CE. T-tests revealed nurses with prior EOL CE scored significantly better than nurses without CE across all survey subsection; nurses who received formal EOL instruction during initial nursing education to score better on objective EOL knowledge/skill questions than nurses without formal EOL education. MANOVAs identified a similar counterintuitive pattern. Bimodal distributions were observed in analyses of "workplace appropriateness" and "desire for education" scores across 23 EOL care topics. Chi-square analyses revealed significant contributions of EOL attitudehelief, prior EOL CE, and objective EOL knowledge/skill toward positive views on EOL workplace appropriateness and desire for EOL education.
Keywords: EOL; End of Life care; Nursing